2019
DOI: 10.1093/nutrit/nuz027
|View full text |Cite
|
Sign up to set email alerts
|

The conundrum of dietary antioxidants in cancer chemotherapy

Abstract: Although chemotherapy succeeds in reducing tumor burden, the efficacy is limited due to acquired drug resistance and often irreparable side effects. Studies show that antioxidants may influence the response to chemotherapy and its side effects, although their use remains controversial. The evidence shows that some chemo-drugs induce oxidative stress and lead to normal tissue apoptosis and the entry of cancer cells to a dormant G0 state. Through the suppression of oxidative stress, antioxidants could protect no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Cancer cells always need to keep an elevated ROS level allowing the pro-tumorigenic cell signaling without inducing cell death. Moreover, the ROS scavenging mechanism is stimulated by tumor cells to maintain ROS levels below the cytotoxic level (Ilghami et al, 2020).…”
Section: Effect Of Reactive Species and Oxidative Stress On Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells always need to keep an elevated ROS level allowing the pro-tumorigenic cell signaling without inducing cell death. Moreover, the ROS scavenging mechanism is stimulated by tumor cells to maintain ROS levels below the cytotoxic level (Ilghami et al, 2020).…”
Section: Effect Of Reactive Species and Oxidative Stress On Cancer Cellsmentioning
confidence: 99%
“…Among them, chemotherapy remains the treatment of choice, integrated with surgery or other therapies. Commonly used chemotherapy drugs are the alkylating agents, anthracyclines (doxorubicin, daunorubicin, epirubicin, idarubicin, aclarubicin, and pirarubicin), epipodophyllotoxines, platinum-based drugs (cisplatin, carboplatin, and oxaliplatin), camptothecins, vinca alkaloids, taxanes, and antimetabolites, which are used for the treatment of a variety of cancers, such as breast, liver, ovarian, testicular, bladder, head and neck, lung cancer (He et al, 2018;Moiseeva, 2019;Ilghami et al, 2020). These drugs can cause more than 40 specific side effects and are broadly categorized into seven types, namely cardiotoxicity, hepatotoxicity, nephrotoxicity, ototoxicity, neurotoxicity, hematological toxicity, and gastrointestinal toxicity.…”
Section: Effect Of Antioxidants In Cancer Therapiesmentioning
confidence: 99%
“…These results could be attributed to better cellular internalization of GO-NEs compared to GO, highlighting the impact of nanoparticles (especially sub 100 nm size) on cellular internalization 40 . Most of the antioxidants induce apoptosis in cancer cells 41 . Our apoptotic assessment results indicated that both GO and GO-NEs were able to induce apoptosis.…”
Section: Rungratanawanich Et Al Investigated the Cellular Antioxidant Activity Of Go And Its Relatedmentioning
confidence: 99%
“…However, antioxidants, when used in therapeutic dose in adjuvant chemotherapy, can hinder this high production of ROS and thus, potentiate the efficacy of cancer treatments, reduce the adverse effects of the therapy and improves the overall health status of the cancer patients. Antioxidants can inhibit cancer proliferation, angiogenesis and metastasis [9]. Dietary antioxidants supplements are frequently in cancer treatment.…”
Section: Role Of Antioxidant In Cancer Therapymentioning
confidence: 99%